A Comparison of the Middle School Science Programmes in Turkey, Singapore and Kazakhstan - Pektaş, Murat; Yazıcıoğlu, Özlem (lnternational Electronic Journal of Elementary Education, 2019)
Comparative education is important for recognising the education systems of different countries, for bringing new practices into the education system and for ensuring educational equality among different societies. This study discusses the education systems of Turkey, Singapore and Kazakhstan. The science curricula of the three countries are compared in terms of their general objectives, processes and skills, areas of learning, measurement and evaluation approaches and achievements. This is a comparative education research with a horizontal approach. The science curriculum of the three countries was used as a data collection tool. As a method of analysis, document analysis was carried out. According to the results of the research, the programmes of all three countries are similar in terms of their general aims, processes and skills, while areas of learning include differences in measurement and evaluation approaches and achievements.
Keywords: 4. Education